La Heterocomposición de las Negociaciones Colectivas de Trabajo: Análisis del Arbitraje Potestativo en los Últimos Años - Ugaz Olivares, Mauro (2015)
This article addresses the issue about the application of Facultative Arbitration and its effect on the redirection of negotiable behaviors of business and gremials organizations in order to achieve some previous agreement before they submitted to an arbitral tribunal. Furthermore, the authors compare the effects of the strike concept variation on the qualification of this like legal or illegal and its relationship with the emergence of Facultative Arbitration that, as an exceptional measure, complement the collective negotiation.